A fully biocompatible single-mode distributed feedback laser. Issue 3 (27th November 2014) - Choi, Yunkyoung; Jeon, Heonsu; Kim, Sunghwan
Abstract : A fully biocompatible laser would be attractive in many aspects of biomedical research. Abstract : A fully biocompatible laser would be attractive in many aspects of biomedical research. Here we report a single-mode biocompatible distributed feedback laser consisting of silk, riboflavin and silver in the form of a freestanding film. The distributed feedback structure has a large surface area and flexibility. The fabricated laser exhibited single-mode lasing at a wavelength of 495 nm.